Pessoa em Bethânia: os versos do desassossego na voz do encantamento - Barros, Andre Luiz Calsone (2013)
The theme Pessoa by Bethânia is the recreation of Caeiro's verses from the performance Rosa dos Ventos- O Show Encantado (Compass Roses - The Enchanted Show), having Maria Bethânia as interpreter. The corpus is the "Poem VIII" from Alberto Caeiro, Fernando Pessoa's heteronym, extracted from the work O Guardador de Rebanhos (The Keeper of Sheep) (1911 - 1912), transformed into a dramatic-musical script, made as a performance during the Compass Rose show. Reinterpreted through voice, body, music and various scenic resources, the poem by Fernando Pessoa wins another dimension in the passage going from text to literary work, in the design of Paul Zumthor, actually, going from the written word in book to bodily presence, updating the virtual scenic and vocals from the preliminary poetic texts. The research aims to answer a key question about the factors that conduct to the redefinition of "Poem VIII" in scenic performance, with the hypothesis that between poem and performance was preserved the same evocation of a new baby Jesus, close, human, simple and pure, stripped of the dogmatic symbolism that the Church imposes to his image and, likewise, it reiterated the role that poet and performer assumed as a kind of "demiurge" not in concept, but in sensations. On the other hand, the "Poem VIII" had lost, in the performance, its desecrating aspect, the high and ironic critic level of dogmas' Church, like the Caeiro's poem presents in the original version. In addition to the concepts of voice, performance, text and work of Paul Zumthor, the concept of "persona", having as a starting point Renato Cohen' studies about the performative act, was extremely important for the analysis of the dramatic-vocal performance of the interpreter Maria Bethânia. The comparative analysis between the poetic text and the passage for its performative work can states the validity of the hypothesis, in order to emphasize a new sacralization, now by the interpreter, invested with an aura that puts her in the intimacy of this new baby Jesus making his alive, every time the show takes place, and, as a ritual, sharing him with the public